The Influence of Learning Interest, Teacher Competence and Learning Facilities on Learning Outcomes during the Covid-19 Pandemic on Economics Subjects at SMA Negeri 1 Rainis - Tirtania Sasea; Olvie Lalamentik; Jerry Wuisang; Edwin Wantah; Johny Taroreh (Jurusan Pendidikan Ekonomi Fakultas Ekonomi dan Bisnis UNIMA, 2022)
Abstract The purpose of this study to determine (1) the effect of interest in learning on learning outcomes during the Covid-19 pandemic on economic subjects at SMA Negeri 1 Rainis, (2) the effect of teacher competence on learning outcomes during the Covid-19 pandemic on economic subjects in SMA Negeri 1 Rainis (3) the effect of learning facilities on student learning outcomes during the Covid-19 pandemic on economic subjects at SMA Negeri 1 Rainis (4) the influence of learning interest, teacher competence and learning facilities on learning outcomes during the Covid-19 pandemic on subjects economics at Rainis 1 Public High School. This research was conducted for about three months. This research is exploratory with descriptive, social and logical causal methods regarding a phenomenon through a number of units or individuals. The results of this study prove that (1) there is a significant influence of the learning interest variable on learning outcomes (2) there isn’t significant effect of the teacher competency variable on learning outcomes (3) there isn’t significant effect of learning facilities on learning outcomes (4) there is a significant effect learning interest variables, teacher competence and learning facilities on learning outcomes. Keywords: interest in learning, teacher competence, learning facilities, learning outcomes Abstrak Tujuan penelitian ini untuk mengetahui (1) pengaruh minat belajar terhadap hasil belajar pada masa pandemi Covid-19 pada mata pelajaran ekonomi di SMA Negeri 1 Rainis, (2) pengaruh kompetensi guru terhadap hasil belajar pada masa pandemi Covid-19 pandemi pada mata pelajaran ekonomi di SMA Negeri 1 Rainis (3) pengaruh fasilitas belajar terhadap hasil belajar siswa pada masa pandemi Covid-19 pada mata pelajaran ekonomi di SMA Negeri 1 Rainis (4) pengaruh minat belajar, kompetensi guru dan fasilitas belajar terhadap hasil belajar selama pandemi Covid-19 pada mata pelajaran ekonomi di SMA Negeri 1 Rainis. Penelitian ini dilakukan selama kurang lebih tiga bulan. Penelitian ini bersifat eksploratif dengan metode deskriptif, sosial dan kausal logis mengenai suatu fenomena melalui sejumlah unit atau individu. Hasil penelitian ini membuktikan bahwa (1) terdapat pengaruh yang signifikan variabel minat belajar terhadap hasil belajar (2) tidak terdapat pengaruh yang signifikan variabel kompetensi guru terhadap hasil belajar (3) tidak terdapat pengaruh yang signifikan antara variabel kompetensi guru terhadap hasil belajar. fasilitas belajar terhadap hasil belajar (4) terdapat pengaruh yang signifikan variabel minat belajar, kompetensi guru dan fasilitas belajar terhadap hasil belajar. Kata kunci: minat belajar, kompetensi guru, fasilitas belajar, hasil belajar